Calculation of resected orbital wall areas in the treatment of endocrine orbitopathy. Issue 4 (April 2017) - Krause, Matthias; Hümpfner-Hierl, Heike; Kruber, Daniel; Sterker, Ina; Hierl, Thomas
Abstract: Purpose: Orbital wall decompression is routinely used to treat proptosis in endocrine orbitopathy. Until now, however, there has been no investigation to measure the area/extent of the removed walls. Materials and methods: The inner areas of 154 orbital walls (lateral, inferior, medial) which had been resected in 38 patients were measured using pre- and postsurgical computed tomographic data in Brainlab iPlan software. Furthermore the effect of concomitant centrolateral orbital rim advancement was calculated in 48 cases. Surgery was performed after preoperative planning using intraoperative navigation. Results: The mean area of resected inferior and medial orbital walls lay at 6.7 cm 2 and 6.2 cm 2, while the area of the lateral orbital wall was 6.9 cm 2 . Rotation-advancement of the lateral rim added an area of 1.8 cm 2 (∼25% of the lateral orbital wall). Comparison of the pre- and postsurgical computed tomographic data showed excellent conformity of the presurgical planning and postsurgical results. Conclusions: This investigation is a first step in analyzing the potential surgical effect of bony decompression surgery by stating the metric amount of orbital wall removal. Using these data, further studies will be performed in the future.